Dampak Pembangunan Infrastruktur Terhadap Kondisi Ketahanan Pangan Di Indonesia (Studi Kasus Provinsi Bali) - Sri Mulyani; Firda Mardhatillah Putri; Bhimo Widyo Andoko; Paisal Akbar; Savira Novalia (Jurnal Ketahanan Nasional, 2020)
ABSTRACT This study had an aim to saw how the impact of infrastructure development on food resilience conditions in Indonesia, focusing on Bali Province. The result of infrastructure development was one of the main factors in realizing the presence of Food Resilience in Indonesia, so the government needed to built supporting infrastructure intended for people who had conditions far from food resilience and good infrastructure. This research used a descriptive method, with taking data from literatur, document, journal, and internet. This study found that the impact of infrastructure development was closely related to the condition of a region's resilience; Bali Province was one of the provinces that had a high food resilence index score, even in the national food resilience index ranking, Bali Province had an index score of 85.15 making Bali Province as the first place in food resilience when compared to other provinces. The food resilience conditions of regencies/cities in Bali Province also showed high index scores; this could be seen in the last two years the position of Denpasar City, Tabanan Regency, Gianyar Regency, and Badung Regency to became cities and regencies that occupied the highest place in the national food resilience index score. Penelitian ini bertujuan untuk melihat bagaimana dampak pembangunan infrastruktur terhadap kondisi ketahanan pangan di Indonesia yang berfokus di Provinsi Bali. Perkembangan pembangunan infrastruktur menjadi salah satu faktor utama untuk mewujudkan hadirnya Ketahanan Pangan di Indonesia, sehingga pemerintah perlu membangun infrastruktur penunjang yang diperuntukkan bagi masyarakat yang memiliki kondisi jauh dari angka ketahanan pangan dan infrastruktur yang baik.Penelitian ini menggunakan metode deskriptif, dengan mengambil data dari kepustakaan, dokumen, jurnal, dan internetPenelitian ini menemukan bahwa dampak pembangunan infrastruktur menjadi sangat berkaitan dengan kondisi ketahanan suatu wilayah, Provinsi Bali menjadi salah satu provinsi yang memiliki skor indeks ketahanan pangan yang tinggi, bahkan dalam ranking indeks ketahanan pangan nasional Provinsi Bali memiliki skor indeks 85,15 menjadikan Provinsi Bali sebagai urutan pertama dalam ketahanan pangan jika dibandingkan dengan provinsi-provinsi lainnya. Kondisi ketahanan pangan kabupaten/kota di Provinsi Bali juga menunjukkan skor indeks yang tinggi, hal ini dapat dilihat dalam 2 tahun terakhir posisi Kota Denpasar, Kabupaten Tabanan, Kabupaten Gianyar dan Kabupaten Badung menjadi kota dan kabupaten yang menduduki posisi teratas dalam skor indeks ketahanan pangan nasional.